Strategy for DNA extraction and detection from insect pests in stored home grain samples (Al-Quds Journal for Natural Sciences, 2021)
Stored grains are subjected to infestations with more than 60 species of insects, that responsible for millions of dollars’ loss and cause several health problems including allergies and gastrointestinal disorders. Traditional detection techniques are laborious, expensive and not sensitive to detect insect contamination at the egg and larvae stages. Therefore, alternative methods are needed for rapid and sensitive detection. One obvious approach is to develop a molecular approach utilizing genetic information of the potential insect species that infest grains for amplification of specific target gene fragment utilizing polymerase chain reaction [PCR]. In the present study, a number of known infested grain samples were used in standardizing a method to isolate larvae and adult insects that were based on centrifugation washing method and a filtration washing method. The isolated insects were subjected to DNA extraction and PCR amplification of defined regions of cytochrome oxidase I (COI) gene followed by sequencing to identify the di"erent pest species. For PCR amplification new primers were designed and for this purpose the obtained COI sequences from di"erent insects were aligned to design two sets of primers (named: COI-PCR4 and COI-PCR5) specific for the indicated insect mitochondrial COI gene. The designed primers were tested for their specificity and sensitivity. The suitability of PCR primers and DNA extraction methods were evaluated on eleven samples of commercial grains utilizing each primer set with the two extraction methods.